Upaya Guru Bimbingan dan Konseling dalam Mencegah Tindakan Cyberbullying - Yeli Amelia; Nabilah Nabilah; Dea Luthfianisa Ishar; Risma Anita Puriani; Rizki Novirson (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to explore the efforts of Guidance and Counseling (BK) teachers in preventing cyberbullying among students through a literature review approach. Cyberbullying has become a serious issue in the educational environment, resulting in significant negative impacts on students' mental health and well-being. This study uses a literature review method, which is an approach that focuses on an in-depth review of various literature sources relevant to the research topic. Through this method, researchers collect, analyze, and synthesize findings from various sources to gain a comprehensive understanding of the strategies implemented by Guidance and Counseling (BK) teachers in dealing with the phenomenon being studied. The findings show that BK teachers play an important role in preventing cyberbullying through several approaches, such as counseling on the dangers of cyberbullying and implementing digital literacy programs. In addition, collaboration with parents and schools was also identified as a key factor in creating a safe environment for students. This study provides valuable insights for educators and stakeholders in developing more effective policies and practices to prevent cyberbullying in schools.